2022
DOI: 10.20944/preprints202207.0448.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Emergence of Automated Vehicles and their Potential Implications for Urban Mobility: A Review of the Literature and Synthesis of Use Cases

Abstract: Automated vehicles (AVs), which are expected to enter the market within the near future, represent the current frontiers in mobility and urban planning. AVs are assumed to bring substantial benefits to cities in many aspects. The present study attempts to investigate this broad assumption by conducting a literature review on the possible implications of AVs in cities as well as synthesizing the current state of practice of AV pilots to detect trends in their deployment. In this paper, literature findings on AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[1,2] AVs as a rapidly growing trend in both research and industry worlds, have the high potential to revolutionize the automotive industry, transportation systems, and the way we live our daily lives. The roots of AVs can be traced back to the early 1920s, [3] gaining momentum in the 1980s when researchers successfully developed automated highway systems. [4] Subsequently, after 2004, the remarkable progress of AVs can be attributed to the extensive research on unmanned equipment conducted by the U.S. Defense Advanced Research Projects Agency, commonly known as DARPA.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] AVs as a rapidly growing trend in both research and industry worlds, have the high potential to revolutionize the automotive industry, transportation systems, and the way we live our daily lives. The roots of AVs can be traced back to the early 1920s, [3] gaining momentum in the 1980s when researchers successfully developed automated highway systems. [4] Subsequently, after 2004, the remarkable progress of AVs can be attributed to the extensive research on unmanned equipment conducted by the U.S. Defense Advanced Research Projects Agency, commonly known as DARPA.…”
Section: Introductionmentioning
confidence: 99%
“…AVs are predicted to hit the market soon and will bring both opportunities and challenges to the road transportation system. According to a recent study by Beza et al [14], the technology has become capable of traversing urban roadways such as roundabouts and pedestrian crossings; however, their operational speed is too low (less than 20 km/h), which is not sufficient for commuters. Furthermore, Zhang and Wang [15] demonstrated that level 4 AV market share in the US cities might reach 34% in 2030 and 75% in 2040.…”
Section: Introductionmentioning
confidence: 99%